2020
DOI: 10.3389/fmicb.2020.593784
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure of Double-Stranded RNA Mycoviruses That Infect the Rice Blast Fungus Magnaporthe oryzae in Japan

Abstract: Various viruses infect Magnaporthe oryzae (syn. Pyricularia oryzae), which is a well-studied fungus that causes rice blast disease. Most research has focused on the discovery of new viruses and the hypovirulence-associated traits conferred by them. Therefore, the diversity and prevalence of viruses in wild fungal populations have not been explored. We conducted a comprehensive screening of M. oryzae mycoviruses from various regions in Japan using double-stranded RNA (dsRNA) electrophoresis and RT-PCR assays. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 59 publications
(89 reference statements)
0
6
0
Order By: Relevance
“…Metatranscriptome sequencing can also alter the diagnosis of a singular infection in fungi to a cryptic co-infection [6,9]. In fact, metatranscriptome sequencing has revealed diverse mycoviruses co-infecting a single isolate of a fungal host and demonstrated that this is a common occurrence [2,[10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metatranscriptome sequencing can also alter the diagnosis of a singular infection in fungi to a cryptic co-infection [6,9]. In fact, metatranscriptome sequencing has revealed diverse mycoviruses co-infecting a single isolate of a fungal host and demonstrated that this is a common occurrence [2,[10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Since the first mycovirus was detected in R. solani in 1978 [27], more than 100 mycoviruses have been identified in this pathogenic fungus [28][29][30][31][32]. To date, the mycoviruses identified in R. solani are double-stranded RNA (dsRNA), positive single-stranded RNA (+ssRNA), or negative single-stranded RNA (−ssRNA) viruses, and include members of established families as well as members of proposed families and unclassified RNA viruses [11], such as Rhizoctonia solani virus 717 (dsRNA, Partitiviridae) [33], Rhizoctonia solani parititivirus 2 (dsRNA, Partitiviridae) [34], Rhizoctonia solani fusarivirus 1 (+ssRNA, proposed family Fusariviridae) [35], Rhizoctonia solani mitovirus 39 (+ssRNA, Mitoviridae) [36], Rhizoctonia solani negative-stranded virus 1 (−ssRNA, proposed family Betamycoserpentoviridae) [12], Rhizoctonia solani mycovirus 2 (dsRNA, proposed family Bipartitiviridae), etc. [37].…”
Section: Introductionmentioning
confidence: 99%
“…Co-infections of mycoviruses are common in plant pathogenic fungi, and the determinants of the assembly rules of the mycovirome are not properly understood but are thought to involve multiple factors such as non-self-recognition, RNA silencing, or a role of nutrients or environmental constraints [48,49]. The biology of the co-infections is still very difficult to study and could be very complex, depending on the fungal host, the nature of the mycoviruses, and the interactions between the co-infecting viruses themselves, ranging from synergism to neutrality, antagonism, or mutualism [50].…”
Section: Discussionmentioning
confidence: 99%
“…Mycoviruses are a group of viruses that infect fungi, whose genomes usually consist of double-stranded (ds) RNA (e.g., families Chrysoviridae, Partitiviridae, Polymycoviridae, and Totiviridae), or single-stranded (ss) RNA (e.g., family Hadakaviridae) [1,22]. Among them, viruses with dsRNA genomes account for the majority of known mycoviruses and are the most studied [19]. Most mycovirus infections are cryptic and have no discernible symptoms.…”
Section: Full Textmentioning
confidence: 99%